Foundations of Chemistry Philosophical, Historical, Educational and Interdisciplinary Studies of Chemistry - Scerri, Eric E. R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Foundations of Chemistry is an international journal which seeks to provide an interdisciplinary forum where chemists, biochemists, philosophers, historians, educators and sociologists with an interest in foundational issues can discuss conceptual and fundamental issues which relate to the `central science' of chemistry. Such issues include the autonomous role of chemistry between physics and biology and the question of the reduction of chemistry to quantum mechanics. The journal will publish peer-reviewed academic articles on a wide range of subdisciplines, among others: chemical models, chemical language, metaphors, and theoretical terms; chemical evolution and artificial self-replication; industrial application, environmental concern, and the social and ethical aspects of chemistry's professionalism; the nature of modeling and the role of instrumentation in chemistry; institutional studies and the nature of explanation in the chemical sciences; theoretical chemistry, molecular structure and chaos; the issue of realism; molecular biology, bio-inorganic chemistry; historical studies on ancient chemistry, medieval chemistry and alchemy; philosophical and historical articles; and material of a didactic nature relating to all topics in the chemical sciences. Foundations of Chemistry plans to feature special issues devoted to particular themes, and will contain book reviews and discussion notes. Audience: chemists, biochemists, philosophers, historians, chemical educators, sociologists, and other scientists with an interest in the foundational issues of science.
Keywords: History; Chemistry; Physical chemistry; Philosophy and science; Philosophy of Science; Chemistry/Food Science, general; History, general; Physical Chemistry